Tensile and thermal properties of natural rubber/ ethylene propylene rubber waste/linear low-density polyethylene blends / Nor Mazlina Abdul Wahab ... [et al.] - Abdul Wahab, Nor Mazlina; Hanapi, Nurin Sabrina; Mustafa, Mohd Syamaizar; Samsudin, Dalina; Ahmad, Zuliahani; Hashim, Faiezah; Sarip, Muhamad Naiman (Penerbit UiTM (UiTM Press), 2025)
Natural rubber (NR) is an isoprene polymer and non-polar rubber obtained from Hevea brasiliensis tree. NR has superior mechanical properties but poor resistance to heat and ozone due to its unsaturation in backbone chain. Ethylene propylene rubber (EPDM) is non-polar rubber which is highly in demand especially in automotive industries because it has high oxidation and ozone cracking resistance since the double bond does not exist in the main backbone chain, leading to high amount of scrap or waste accumulated by time. Thus, this research embarks to use the blend of NR/EPDM in addressing green environment. However, the blend of this material leads to phase separation and poor interfacial adhesion, resulting in a heterogeneous blend that possesses poor compatibility. Hence, linear low-density polyethylene (LLDPE) is used as a compatibilizer and additive in this blend. The ternary blends NR/EPDMw/LLDPE blend were prepared in an internal mixer at approximately 160 °C. The amount of EPDMw was fixed at 60 phr, but NR and LLDPE were manipulated. The blend compositions of the ternary blend were 40/60/0, 35/60/5, 30/60/10, 25/60/15, and 20/60/20 (phr) of NR/EPDMw/LLDPE, respectively. The effects of the partial replacement of NR by LLDPE on compatibility, tensile and thermal properties were studied using tensile testing, DSC and TGA. The results showed that the ternary blend was partially miscible, and the 30/60/10 blend composition had better compatibility compared to other compositions, which was indicated by an increment of tensile strength and elongation at break, with 11.33 MPa and 270.66%, respectively than that of the control sample. Adding LLDPE to an NR/EPDMw blend increased the Tm, but further increasing LLDPE from 10 to 20 phr and it did not significantly affect the Tm, which remained unchanged. It also showed that the crystallinity and thermal stability of the blend increased as LLDPE content in the blends increased. This was because the presence of LLDPE improved the melting enthalpy and crystallinity of the blend. As the LLDPE content increased, it restricted the mobility of polymer chains and lowered thermal vibrations in C-C bonds, enhancing thermal stability. Overall, the addition of LLDPE content improved the compatibility and thermal stability of NR/EPDMw blends.